Liberation Through Narrativity: A Case of Organization Reconstruction Through Strategic Storytelling - ARNAUD, Nicolas; MILLS, Colleen; LEGRAND, Céline (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2016)
This paper examines the ebb and flow of organizational power and control during an organizational change where a CEO mobilized narratives to liberate his company from top-down control. The emergent conceptual model makes sense of what appears to be discursive disorder – a cacophony of change narratives. Its contribution is twofold. Firstly, by identifying three ‘narratives in the making’ – the initial, counter and corrective narratives, it elaborates the meso-level narrative mechanisms at the heart of discursive struggles during change and extends Boje’s (2010) triad of narrativity. Secondly, it confirms the utility of the ‘organizational becoming’ and CCO perspectives of organizing for understanding change.